Modification of banana starch (Musa paradisiaca L.) with polyethylene terephthalate: Virgin and bottle waste - Ramírez-Centeno, Silvia; Marcos-Fernández, Ángel; Aparicio Saguilan, Alejandro; Navarro-Crespo, Rodrigo; Ramírez Hernández, Aurelio; Báez-García, Eduardo; Páramo Calderón, Delia Esther (Carbohydrate Research, 2021)
Chemical modification of banana starch (Musa paradisiaca L.) with the degradation products of virgin and bottle waste of polyethylene terephthalate was carried out in situ. The modified starch was characterized by FTIR and NMR, which allowed proposing three chemical structures. SEM micrographs showed that the morphology of the modified starch granule is directly related with mass ratio of Starch/PET and type of PET used in the reaction. The crystallinity of the modified starch decreased up to 92.6% and 62.5% using bottle waste and virgin PET, respectively, according to XRD diffractograms. TGA analysis showed that the starch degradation temperature decreased by 12 °C. Modified starch films were elaborate and its electrical conductivity was found to be 2.9 times compared to that of native starch. The starch/PET film presented the highest value in the mechanical property of elongation at break compared to the starch-only film. The modified starch film was degraded above 80% by aqueous hydrolysis.
Keywords: Almidón de plátano; Modificación química; Musa paradisiaca L.; Película biodegradable